RESIDENTIAL SCALE CENTALIZED DOMESTIC WASTE WATER MANAGEMENT SYSTEM PLANNING IN RPTRA PULO GUNDUL, CENTRAL JAKARTA - Maria Scriftura Sinaga, Hanna
. Domestic wastewater in Pulo Gundul residence has not been properly managed, where greywater is discharged directly into water bodies or soil without treatment, thus polluting surface water. In realizing proper sanitation, it will be planned to build a communal wastewater treatment plant in the form of sewerage system plan and appropriate alternative technology for the regional and community conditions of the Pulo Gundul area, Central Jakarta. With the scope of existing limitations, especially land limitations, a communal domestic wastewater management system will be planned with several alternative pathways and technologies such as Anaerobic-Aerobic biofilter, Moving Bed Biofilm Reactor (MBBR), and Anaerobic-Anoxic-Aerobic Membrane Biofilter (A2O-MBR) which will be analyzed using the SAW (Simple Additive Weigh) method. The design stage is carried out by identifying the problem and solving the problem. The sewerage system plan will serve 52.98% of the population of the service area in 2032 and 100% in 2042. The pipe diameters used are 114 mm and 127 mm. Based on the maximum daily discharge and infiltration discharge from the SPAL calculation, an WWTP will be built with a processing discharge of 178 m3 /day with a gradual development, namely 1 Aerobic-Anaerobic Biofilter unit with a capacity of 89 m3 /day in planning 2032 and the addition of 1 twin unit in planning 2042. In this study, an analysis of Ability to Pay (ATP) and Willingness to Pay (WTP) was carried out in determining community retribution rates.